(untitled) (Journal of the College of Basic Education, 2022)
The receptive theory is considered one of the leading theories in modern critical discourse, based on its interest in the forum and not the creator, as well as its inclusion in all creative works from poetry to theater to novel to article, as well as its entry into analytical parts that may not be reached by the rest of the literary genres, and we have observed through a scientific experience Modestly, this theory is suitable for being the pioneer of modern critical approaches in modern human creative analysis, especially since this theory has roots in Ancient Arab criticism.